Effect of high-temperature stress on microalgae at the end of the logarithmic phase for the efficient production of lipid. Issue 20 (17th October 2016) - Han, Fei; Pei, Haiyan; Hu, Wenrong; Han, Lin; Zhang, Shuo; Ma, Guixia
ABSTRACT: Efficient production of microalgae lipid is significant for the production of renewable biodiesel. In the present study, the high temperature of 40°C as stress environment was tested for stimulating lipid accumulation after the microalgae ( Scenedesmus quadricauda ) cells in suitable conditions grew to the end of the logarithmic phase. Different stress cultivation times of 1, 2, 3, 4, 5 and 6 days were studied. Interestingly, the lipid content and productivity reached 33.5% and 23.2 mg/L d after one day stress cultivation, showing substantial improvements of 39.6% and 33.3% compared with that in the untreated (day 0) microalgae cells, respectively. Longer stress time led to the decrease of biomass and lipid content compared with the untreated microalgae. However, a maximum protein content of 58.7% was obtained after six days. The stress cultivation at the end of the microalgae exponential phase for one day at a high temperature of 40°C could be a very useful industrial approach for efficiently promoting lipid content and biodiesel production.